2023
DOI: 10.1055/a-2072-2177
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of Nothapodytes tomentosa and Distribution and Content of Camptothecin and its Analogues in Four Plants

Abstract: Camptothecin (CPT) and its derivatives have attracted worldwide attention due to their notable anticancer activity. However, the growing demand for CPT in the global pharmaceutical industry has caused a severe shortage of CPT-producing plant resources. In this study, phytochemical analysis of Nothapodytes tomentosa resulted in the isolation and identification of CPT (13) and 16 analogues (1-12, 14-17), including a new (1) and five known (9, 10, 12, 15 and 17) CPT analogues with an open E-ring. In view of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…In this process, a set of well-characterized natural biosynthetic enzymes are fundamental components, although some artificial enzymes with high catalytic efficiency have been synthesized (Huang et al, 2021). Our earlier research revealed a relatively high content of C-9 hydroxylated CPT derivatives in N. tomentosa (Li et al, 2023), resulting in the inaugural report of the isolation of 9-HCPT from a plant source. These findings underscore the potential for developing synthetic biology approaches to introduce C-9 decorations on CPT using natural biosynthetic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this process, a set of well-characterized natural biosynthetic enzymes are fundamental components, although some artificial enzymes with high catalytic efficiency have been synthesized (Huang et al, 2021). Our earlier research revealed a relatively high content of C-9 hydroxylated CPT derivatives in N. tomentosa (Li et al, 2023), resulting in the inaugural report of the isolation of 9-HCPT from a plant source. These findings underscore the potential for developing synthetic biology approaches to introduce C-9 decorations on CPT using natural biosynthetic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…C amptothecin (CPT) is a structurally unique monoterpenoid indole alkaloid found in a number of angiosperm plants, including Camptotheca acuminata (Nyssaceae), Nothapodytes tomentosa (Icacinaceae), and Ophiorrhiza pumila (Rubiaceae), among others (Pu et al, 2019;Li et al, 2023). Camptothecin has become increasingly relevant due to its extraordinary antitumor activity, which occurs through the selective inhibition of DNA topoisomerase I and induction of protein-linked DNA complex breaks (Hsiang et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation